Similarity effects of two types of adaptogens (transcutaneous electrical stimulation with the device “VEB” ® and using of bioactive Naftussya water) on the human body - Popovych, Igor (Journal of Education, Health and Sport, 2022)
Background. The studies of the Truskavetsian Scientific School of Balneology have shown that both the Naftussya bioactive water and the standard balneotherapy complex (Naftussya drink, ozokerite applications, mineral baths) exhibit the properties of adaptogens, similar to such ginseng and phytocompositions. At the same time, in the process of researching the influence of devices for transcutaneous electrical stimulation on the human body, we found that changes in the parameters of the neuro-endocrine-immune complex and metabolism also have an adaptogenic character. The purpose of this study is to find effects common to adaptogens of chemical and physical nature. Materials and Methods. The object of observation were 29 women 30-76 (50±13) y and 28 men 25-69 (48±13) y without a clinical diagnosis, but with the deviations from the norm in a number of parameters of the neuro-endocrine-immune complex as a manifestation of dysadaptation. Parameters of biophotonics, acupuncture points, EEG, HRV, immunity, metabolism, blood pressure and hormones levels before and after a four-day transcutaneous electrical stimulation session or one-week course of drinking of Naftussya water registered. Results. Screening revealed that 43 variables respond to the action of adaptogens according to the law of the initial level, at the same time, 4 initially elevated and 9 normal variables show further growth. Caused by adaptogens changes in 7 EEG and 7 HRV parameters determine favorable changes in 2 endocrine, 10 immune, 3 metabolic, 2 hemodynamic and 3 biophotonics parameters by 83,5%. Conclusion. The adaptogens both of chemical and physical nature, activating the receptors of the gut mucosa or the skin, respectively, have similar favorable effects on the parameters of the neuroendocrine-immune complex, metabolism, hemodynamics and biophotonics.